ADVERTISING AND SIGNBOARDS AS A REFLECTION OF ATTITUDES TOWARD LANGUAGE (International journal of artificial intelligence, 2026)
This article examines the role of advertisements and signboards in shaping and reflecting public attitudes toward language. In modern society, linguistic culture is not only preserved in literature and education, but also manifested in everyday public texts such as commercial advertisements, street signs, shop names, and information boards. The study analyzes the linguistic quality of advertising texts, the influence of globalization on language use, and the social consequences of neglecting linguistic norms. Special attention is given to the relationship between language accuracy and cultural identity. The article also discusses the responsibility of businesses, media representatives, and educational institutions in maintaining linguistic standards in public communication.